Questions of Cluster Interaction of Tourism Development along the Silk Road - SADUOV, Askar; MUKANOV, Beibut; ASANOVA, Maral; RAKHIMZHANOVA, Raushan; RAIMBEKOV, Bagdat (Journal of Environmental Management and Tourism; Vol 10 No 6 (2019): JEMT Volume X Issue 6(38) Fall 2019DO - 10.14505//jemt.v10.6(38).05, 2019)
The article proposes a tour that combines visits to all these clusters, when cluster unification in the Association, the creation of networks of partners in the republic can turn a disadvantage into an advantage, when tourists are not divided, but multiplied by passing each other, offering additional services. The use of several tourist clusters in one major tour will lead to a uniform workload of clusters, advertising less well-known tourist clusters through the more famous ones. Their recognition by foreign tourists. Each cluster has its own specific services. The use of several clusters will increase the range of services; thereby better meet the diverse needs of tourists. Organizing a tour across several clusters will allow the tour to include the best services from each cluster, which will increase the competitiveness of the Kazakhstan tour in the international arena. I.e., in the formation of a competitive international tour will involve the forces of not one, but several regions at once. The tour will use the facilities of both tourist infrastructure and other industries. This will result from the multiplicative and synergistic effect of the development of several industries. Increasing the popularity of the tourism industry in Kazakhstan on the international tourism market will lead to attracting international investment in other sectors of Kazakhstan, due to the development of business, congress and other types of tourism.